Severe Pancytopenia Induced by Low-dose Methotrexate in a Hemodialysis Patient - Yigit, Irem Pembegul; Ulu, Ramazan; Yildiz, Yener; Dogukan, Ayhan; Celiker, Hueyin (Turk Nefroloji Diyaliz Transplantasyon Dergisi, 2010)
Methotrexate has been used as an important alternative therapy in the treatment of various rheumatic diseases. It is primarily cleared by the kidney. Life-threatening marrow suppression in hemodialysis patients has been reported. A 35-year-old woman undergoing hemodialysis developed severe stomatitis and pancytopenia after low-dose methotrexate treatment for rheumatoid arthritis. She recovered after folinic acid, granulocyte colony-stimulating factor, antibiotic and daily hemodialysis therapy.
Keywords: Methotrexate; Hemodialysis; Pancytopenia